2021
DOI: 10.1021/acs.inorgchem.0c02648
|View full text |Cite
|
Sign up to set email alerts
|

Organoplatinum(II) Complexes Self-Assemble and Recognize AT-Rich Duplex DNA Sequences

Abstract: The specific recognition of AT-rich DNA sequences opens up the door to promising diagnostic and/or therapeutic strategies against generelated diseases. Here, we demonstrate that amphiphilic Pt II complexes of the type [Pt(dmba)(N∧N)]NO 3 (dmba = N,N-dimethylbenzylamine-κN, κC; N∧N = dpq (3), dppz (4), and dppn ( 5)) recognize AT-rich oligonucleotides over other types of DNA, RNA, and model proteins. The crystal structure of 4 shows the presence of significant π-stacking interactions and a distorted coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…These results indicated that all of the compounds were stable at least for 48 h in the buffer solution. 31 HPLC was also used to study the stability and purity of the test compounds. HPLC analysis of the solutions at 0 h and 48 h was carried out at room temperature.…”
Section: Stability and Purity Of Complexes 1-4 In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that all of the compounds were stable at least for 48 h in the buffer solution. 31 HPLC was also used to study the stability and purity of the test compounds. HPLC analysis of the solutions at 0 h and 48 h was carried out at room temperature.…”
Section: Stability and Purity Of Complexes 1-4 In Solutionmentioning
confidence: 99%
“…S10 †), indicating that the ligands and complexes were stable in the Tris-HCl solution for at least 48 h. The HPLC results were consistent with the UV-Vis analysis results. 31…”
Section: Stability and Purity Of Complexes 1-4 In Solutionmentioning
confidence: 99%
“…Indeed, this peculiar ligand has been largely exploited not only to improve the photobiological activity of the resulting compounds, via the population of long-lived dppn-centered 3 ππ* excited states, but also to shift their 1 MLCT absorption towards longer wavelengths 18 and, given its known DNA-intercalating properties, to strengthen their interaction with the nucleic acid. 19–21 A recent example of this was reported by Zhao and coworkers, who showed the benefits derived from the substitution of a bpy (bipyridine) unit by a dppn ligand in their tris-heteroleptic RPC-based PSs. 22…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, this peculiar ligand has been largely exploited not only to improve the photobiological activity of the resulting compounds, via the population of long-lived dppn-centered 3 ππ* excited states, but also to shift their 1 MLCT absorption towards longer wavelengths 18 and, given its known DNA-intercalating properties, to strengthen their interaction with the nucleic acid. [19][20][21] A recent example of this was reported by Zhao and coworkers, who showed the benefits derived from the substitution of a bpy (bipyridine) unit by a dppn ligand in their tris-heteroleptic RPC-based PSs. 22 Notwithstanding the advantages derived from the use of dppn, it is surprising that PSs containing two dppn ligands simultaneously coordinated to a Ru(II) center have been only sparingly explored, 23,24 while numerous examples of dppn-containing RPCs for PDT are reported in the literature [25][26][27][28][29][30][31] (some of them have also been applied for compounds at the boundary between PDT and photoactivated chemotherapy PACT).…”
Section: Introductionmentioning
confidence: 99%
“…[12] The interesting point about arylplatinum complexes containing chelating ligands is the formation of square planar geometry, which can have appropriate interactions with DNA. [13][14][15][16] It was shown that some platinum complexes can interact with the double helix of DNA through various modes such as intercalation (binding between two base pairs), electrostatic interaction, and groove binding. [17] So, the pharmaceutical and biological properties of Pt complexes are attributed to the binding modes with DNA.…”
Section: Introductionmentioning
confidence: 99%